The role of CCL25 and CCR9 in intestinal inflammation - Wendt, E; Emily Rose Wendt (2013)
Leukocyte extravasation is mediated in part by tissue specific chemotactic cytokines (chemokines) and specific chemokine receptors expressed on the surface of circulating cells. C-C chemokine ligand CCL25 is expressed exclusively in the intestine and thymus and mediates chemotaxis by cells expressing receptor CCR9. This chemokine and receptor pair may be relevant in the pathogenesis of intestinal inflammation, in diseases such as Crohn’s disease (CD) and coeliac disease. In this thesis I investigated CCR9 expression in situ, in tissues affected by intestinal inflammation, and also examined the effects of CCR9 antagonist treatment in patients. In vitro I investigated CCR9 function using human peripheral blood T cells enriched for CCR9 by cell sorting or all-trans retinoic acid treatment. Using tissues collected as part of a clinical trial in CD testing CCR9 antagonist, CCX282-B, I investigated ways of measuring if treatment reduced the number of CCR9 expressing cells in the intestinal mucosa. However, in situ staining for CCR9 by immunohistochemistry was unsuccessful, and in this thesis, I explored reasons why this might be the case. Treatment with CCX282-B did however, show a tendency to reduce T cell density in the intestinal mucosa, although results were highly variable between individuals. In an examination of human CCR9 function in vitro I demonstrate for the first time that CCL25 stimulates CCR9 surface internalization. These data clarify the observation that CCR9 staining by IHC produces poor results in tissues where ligand is abundant, such as the intestine and thymus. I describe a novel technique for measuring calcium flux in two populations simultaneously by flow cytometry, which confirmed that in a heterogeneous population of cells, only CCR9 expressing cells respond to CCL25 by calcium flux. Variability in clinical trials is partly created by the use of concomitant medications, and in CD, corticosteroids are widely used. For the first time I show that glucocorticoids (GC) impair CCR9 mediated chemotaxis, calcium flux and intracellular signalling without changes to CCR9 mRNA and surface protein expression. Reduced CCR9 mediated signalling was accompanied by an enhanced expression and function of co-expressed CXCR4, demonstrating that the effects of GC were receptor-specific and not mediated by non-specific toxicity or inhibition of cell signalling. In a second study CCX282-B was tested in patients with coeliac disease, and in this trial, there was no reported concomitant use of GCs. It was confirmed that dietary gluten stimulates significant T cell recruitment to the intestinal mucosa with a pronounced accumulation of intraepithelial lymphocytes (IEL) and a rise in the frequency of FoxP3 expressing cells. Patients on CCX282-B had lower IEL counts, and an equivalent proportion of FoxP3 expressing T cells, suggesting that CCR9 blockade restricted the recruitment of effector T cell subsets. This thesis confirms that the accumulation of T cells is central to inflammation in the intestine and that modulating chemokine receptor function may affect this. Furthermore, this thesis demonstrates that the function of CCR9 is suppressed by GCs, which are widely used therapeutically and therefore could identify a novel mechanistic basis for their activity in CD.